2016
DOI: 10.1136/bmjquality.u217936.w7106
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the incidence of Obstetric Sphincter Injuries using a hands-on technique: an interventional quality improvement project

Abstract: A main concern for women giving birth is the risk of obstetric anal sphincter injuries. In our department the incidence of sphincter injuries was around 8 % among vaginally delivering first time mothers. We aimed to halve the incidence to 4 % or less. A prospective interventional program was instituted. We implemented a hands-on technique with four elements in a bundle of care together with a certification process for all staff on the delivery ward. The incidence of episiotomies served as a balancing indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
5
18
0
1
Order By: Relevance
“…Episiotomy also has associated morbidity including hemorrhage, pain, and wound infection or breakdown . The present results are consistent with another report indicating that modification of second stage practices does not need to be associated with an increase in episiotomy in order to decrease OASI rates …”
Section: Discussionsupporting
confidence: 91%
“…Episiotomy also has associated morbidity including hemorrhage, pain, and wound infection or breakdown . The present results are consistent with another report indicating that modification of second stage practices does not need to be associated with an increase in episiotomy in order to decrease OASI rates …”
Section: Discussionsupporting
confidence: 91%
“…13 The convincing large-scale observational data with substantial reduction in the incidence of OASIS in Norway due to a national strategy of OASIS prevention inspired several departments in Denmark to initiate local prevention programs. 18,19 In Norway, there was a significant decrease from 4%-5% to 1%-2% OASIS in all vaginal deliveries. 20,21 At one of the hospitals in Norway the incidence of OASIS decreased from 4% to 1% over a few years after adopting the Norwegian/Finnish model.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis for this could be a previous tendency towards “hands off” the perineum; another could be the increased focus on diagnosing and coding of OASIS . The convincing large‐scale observational data with substantial reduction in the incidence of OASIS in Norway due to a national strategy of OASIS prevention inspired several departments in Denmark to initiate local prevention programs . In Norway, there was a significant decrease from 4%‐5% to 1%‐2% OASIS in all vaginal deliveries .…”
Section: Discussionmentioning
confidence: 99%
“…In the previously published article covering the quality improvement methodology of the trial, we included descriptive statistics on the adherence to process indicators and the corresponding chronology of the outcome measure. 18 The present study includes original descriptive data on the cohorts before and after initiation of the intervention, and analysis of the correlation among the five different elements of the care bundle and the outcome, including a regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Using a quality improvement framework with documentation of the use of the elements of the care bundle, we showed that it was feasible to implement a standardized hands-on technique in vaginal delivery, thereby significantly reducing the incidence of OASIS from 7 to 3.4%. 18 In the present study, we aimed at analyzing the association between each element of the intervention and the outcome.…”
mentioning
confidence: 99%